PELATIHAN PENERAPAN SANITASI HYGIENE PRODUK OLAHAN HASIL PERIKANAN DI DESA AENG DAKE KABUPATEN SUMENEP PROVINSI JAWA TIMUR - Mubarak, Ahmad Shofy; Saputra, Eka; Pujiastuti, Dwi Yuli (Jurnal Abdi Insani, 2024)
Sumenep Regency is one of the contributors to seaweed production in Indonesia and is classified as a Minapolitan location. One of the seaweed producing districts is Aeng Dake Village, Bluto District. The problem that arises is that there is no food safety system. This results in the product not being able to compete with other products that already implement food safety. So if it enters a wider market, both national and international, the product will experience rejection. This activity aims to apply appropriate technology in implementing sanitation and hygiene to reduce contaminants so that consumers will feel safe regarding the products produced. Community service is carried out through packaging design training activities and creating online marketing media via websites and social media. Namely by providing workshops packaged online using the zoom application (due to the corona pandemic) including material, discussions and simulations of implementing sanitation. Partners still produce processed products on a small scale and are not yet standardized in the field of food safety. This problem results in the product not being able to compete with other products that already implement food safety. Food safety system problems, namely sanitation and hygiene, can be solved by providing training on the concept of sanitation and hygiene, including theory and practical application in the production process flow. The problem of determining shelf life can be solved by training in determining shelf life including theory and practice that can predict product shelf life. It is hoped that the direct practice given to the processing group will provide skills in analyzing and determining the shelf life of products independently.